OS TERRITÓRIOS DE GOVERNANÇA E SUAS REDES GEOGRÁFICAS: ESTUDOS SOBRE O DESENVOLVIMENTO DO TURISMO RURAL NOS CAMPOS GERAIS/PR, BRASIL E COMUNIDADE AUTÔNOMA DE ARAGÃO, ESPANHA - Santos, Silvana Kloster dos (2017)
This work aims at studying regional tourism governance in two different areas: Campos Gerais, in Paraná State, Brazil and Aragão, Spain. Taking into consideration projects which are mobilizing several local actors for the development of Rural Tourism. For that, it was necessary to discuss the integration of the concepts of territory and geographic networks in connection with tourism. It also sought to contextualize the formation of regional governance models in both regions, mainly, analyzing the organizational systems of these models.To supplement the information, it was described the profile of rural tourism projects and ventures in both territories. Therefore, the thesis was carried out in three stages. In the first stage, it was including the theoretical deepening, having such as subjects the integrative perspective of the territory, tourism in the territory, governance and, finally, rural tourism. In the second stage, it was described the field researches based in recorded interviews with the public agents and farmers involved in the rural tourism activity. And in the last step, it was used the DAFO system and Content Analysis by evocations. It was also necessary used of the integrative perspective as concept, gives thereby different social dimensions capable of playing the role of region such as an integrating concept. Furthermore, tourism is an important agent of alteration of the territory and its networks are used for its fluidity, being these, a determining factor as instrument of power and selection of places for the tourism.The governance is the network that connects and articulates different points or 'nodes' formed by agents that operate within a collective order. It is also responsible for coordinating, directing and articulating actions within its space. Usually, rural tourism is seen as an 'alternative' activity, capable of development the rural territories in an integrated way, valuing economic, social and cultural aspects, being considered a possible solution for rural exodus problems. Additionally, it was found that there are accentuate gaps between the governance and their geographic networks, for example, in one of the networks there is little connection and exchanges, while in the other, these exchanges are fluid and occur rapidly. Thus, the work emphasizes the importance of the existence of specific public policies for rural tourism and how they can help in the implementation of financial resources, and in the interaction and commitment of the actors involved in the rural tourism activity.